SYSTEM FACTORS OF DEVELOPMENT STRATEGIES OF ENERGY-SAVING ADAPTIVE-EXTREME AUTOMATION SYSTEMS IN THE ELECTROMETALLURGY - Труфанов, Иван Дмитриевич; Лютый, Александр Павлович; Чумаков, Кирилл Игоревич; Поляков, Михаил Алексеевич; Близняков, Александр Викторович; Кащук, Инна Алексеевна (Eastern-European Journal of Enterprise Technologies, 2010)
On the basis of electro-economical efficiency of implementing an Energy-saving Programme (1997-2010) analysis innovative hierarchical externally - adaptive automated electro steel melting automatization systems system technical synthesis is fulfilled in operating electro metallurgical production conditions.